2014
DOI: 10.1073/pnas.1321745111
|View full text |Cite
|
Sign up to set email alerts
|

Human coding RNA editing is generally nonadaptive

Abstract: Impairment of RNA editing at a handful of coding sites causes severe disorders, prompting the view that coding RNA editing is highly advantageous. Recent genomic studies have expanded the list of human coding RNA editing sites by more than 100 times, raising the question of how common advantageous RNA editing is. Analyzing 1,783 human coding A-to-G editing sites, we show that both the frequency and level of RNA editing decrease as the importance of a site or gene increases; that during evolution, edited As are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
132
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(158 citation statements)
references
References 49 publications
(104 reference statements)
15
132
4
Order By: Relevance
“…It has been shown that at least 40% of miRNAs have altered levels in ADAR mutant C. elegans strains, although editing in small RNAs is rare [20]. Interestingly, a recent report found that despite the presence of a few sites in which editing is clearly beneficial, human RNA editing sites in coding regions are generally nonadaptive and evolutionarily poorly conserved, arguing against the physiological significance of these editing events in human [56]. Strikingly, the observations that ADAR1-deficient mice exhibited embryonic lethality [23][24][25] and that ADAR1 KD hESCs exhibited significant differentiation defects (Figure 1) clearly demonstrate that ADAR1 is highly likely to be crucial for mammals.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that at least 40% of miRNAs have altered levels in ADAR mutant C. elegans strains, although editing in small RNAs is rare [20]. Interestingly, a recent report found that despite the presence of a few sites in which editing is clearly beneficial, human RNA editing sites in coding regions are generally nonadaptive and evolutionarily poorly conserved, arguing against the physiological significance of these editing events in human [56]. Strikingly, the observations that ADAR1-deficient mice exhibited embryonic lethality [23][24][25] and that ADAR1 KD hESCs exhibited significant differentiation defects (Figure 1) clearly demonstrate that ADAR1 is highly likely to be crucial for mammals.…”
Section: Discussionmentioning
confidence: 99%
“…A recent compilation of human RNA editing sites, generated from multiple studies, estimated that there were ∼1200 in total (Xu and Zhang, 2014). Most of the sites, however, only occurred in a single sample and at very low frequency.…”
Section: Adars Do Much More Than Alter Codonsmentioning
confidence: 99%
“…Guixia Xu and Jianzhi Zhang create a compelling argument that RNA editing is generally not used for adaptation in mammals (Xu and Zhang, 2014). In their study, the authors tabulated all the human recoding events in coding regions and found that, after normalizing for the abundance of adenosine targets, non-synonymous edits were less frequent than expected and synonymous changes more frequent.…”
Section: Cephalopod Rna Editing Breaks the Rulesmentioning
confidence: 99%
“…This observation suggests that the presence of an editing event within an RNA is more important than the precise location of that event, supporting the hypothesis that editing has a function beyond recoding RNAs. Furthermore, it is unlikely that ADAR evolved primarily to diversify the coding potential of mRNAs as most editing in human coding sequences does not confer an adaptive advantage (Xu and Zhang 2014). Rather, it is postulated that ADAR had an unknown ancestral function and later evolved to target the codons of particular transcripts (Bass 2002;Gray 2012;Xu and Zhang 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is unlikely that ADAR evolved primarily to diversify the coding potential of mRNAs as most editing in human coding sequences does not confer an adaptive advantage (Xu and Zhang 2014). Rather, it is postulated that ADAR had an unknown ancestral function and later evolved to target the codons of particular transcripts (Bass 2002;Gray 2012;Xu and Zhang 2014). Although a few studies have reported specific roles for A-to-I editing beyond recoding, including influencing RNA stability (Scadden and Smith 1997;Scadden 2005) and driving nuclear localization (Zhang and Carmichael 2001), these roles have not proven widely generalizable (Hundley and Bass 2010;Nishikura 2010).…”
Section: Introductionmentioning
confidence: 99%